Pengaruh Live Streaming Instagram Dan Kualitas Produk terhadap Keputusan Pembelian Konsumen Babe_Boku di Bondowoso (Jurnal Strategi dan Bisnis, 2023)
This study aims to examine the effect of Instagram live streaming and product quality on purchasing decisions. This type of research is quantitative research. The sample in this study was obtained using a purposive sampling method, namely selecting a sample using predetermined criteria. Based on the purposive sampling method, a total of 100 samples were obtained from respondents who had made purchases of Babe_boku goods that were promoted via Instagram live streaming. The type of data used is primary and secondary data. The analytical method used in this study is multiple linear regression analysis using the SPSS version 22 program. The results of this study indicate that Instagram live streaming and product quality have a significant effect on product quality.